Pengembangan Sistem Pakar Diagnosa Kanker dan GERD Berbasis Website - Aprilia Adelina Roring; Gilbert Josua Mangkay; Jean Stella Saragih; Ricat Abetnego Sundari; Jhosua Allesandro Tingon; Paul Aleksander Mundung; Yulisa Aprianti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Cancer and Gastroesophageal Reflux Disease (GERD) are serious health problems whose early detection is often hampered by limited access and awareness. This research aims to develop a website-based expert system as a solution to help the public perform an initial diagnosis of cancer and GERD independently. The system development methodology includes a requirements analysis phase, data flow design using DFD and ERD, and implementation using Visual Studio Code with programming languages such as Python and JavaScript, along with a MySQL database. The result of this research is a functional web-based expert system equipped with various features, including user registration, a structured diagnostic questionnaire for cancer and GERD, a diagnosis result page complete with recommendations, and a statistics module for data visualization. This system successfully provides an easily accessible platform for initial diagnosis, despite having limitations related to accuracy, which depends on user input. In conclusion, this expert system has the potential to be an effective initial screening tool for increasing awareness and accelerating the management of these two diseases